Experiências de violência de mulheres em situação de rua: um estudo de casos múltiplos - Santos, Bianca Correa dos (Universidade Federal de São Carlos, 2023)
The vulnerability context faced by individuals experiencing homelessness, coupled with a patriarchal societal model, exposes women living on the streets to various forms of violence. In this regard, the present study aimed to analyze and reflect upon the experiences of violence endured by women in situations of homelessness. Two participants, one cisgender and one transgender, both experiencing homelessness for at least a month and aged over 18, took part in this research. They responded to a semi-structured interview conducted during a meeting held at a sheltering institution. The gathered information was transcribed and subjected to thematic analysis to identify convergent and divergent content in the participants' narratives and to establish analytical categories. Their past histories and the factors leading to homelessness were linked to adverse childhood experiences. Both had suffered violence from intimate partners and were drug users. The perception of violence experienced and witnessed in the context of homelessness was associated with various forms of violence primarily perpetrated by other men, within the framework of vulnerability and gender inequality.
Women's experiences of violence in street situations: a multiple case study
Keywords: Mulheres; Situação de Rua; Violência; Women; Homelessness; Violence; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA SOCIAL::PAPEIS E ESTRUTURAS SOCIAIS; INDIVIDUO